Pericardial Decompression Syndrome: A Comprehensive Review of a Controversial Entity - Sarode, Karan; Patel, Amar; Arrington, Kedzie; Makhija, Rakhee; Mukherjee, Debabrata (International Journal of Angiology, 2024)
Pericardial decompression syndrome is an ambiguous clinical entity which has generated controversy regarding its existence. Following pericardial decompression, patients experienced clinical deterioration ranging in complications from pulmonary edema to death that could not be attributed to any other distinct clinical pathology. Multiple theories have suggested the pathophysiology behind pericardial decompression syndrome is related to preload-afterload mismatch following pericardial decompression, coronary microvascular ischemia, and stress from high adrenergic state. Our review aims to describe this syndrome by analyzing demographics, etiology of pericardial effusion, method of drainage, volume of pericardial fluid removed, time to decompensation, and clinical outcomes. A systematic review of MEDLINE/PubMed and Google Scholar literature databases were queried for case reports, case series, review articles, and abstracts published in English journals between 1983 and December 2022. Each author's interpretation of echocardiographic and/or pulmonary arterial catheterization data provided in the case reports was used to characterize ventricular dysfunction. Based on our inclusion criteria, 72 cases of pericardial decompression syndrome were included in our review. Our results showed that phenotypic heterogeneity was present based on echocardiographic findings of right/left or biventricular failure with similar proportions in each type of ventricular dysfunction. Time to decompensation was similar between immediate, subacute, and acute cases with presentation varying between hypoxic respiratory failure and shock. This review article highlights theories behind the pathophysiology, clinical outcomes, and therapeutic options in this high mortality condition.
Keywords: cardiovascular disease; pericardiocentesis; cardiac tamponade; pericardiostomy; pericardial decompression syndrome; shock; ischemia